Pengaruh Reputasi Underwriter, Reputasi Auditor, dan Ukuran Perusahaan terhadap Underpricing Perusahaan yang Melakukan Initial Public Offering (IPO) di BEI - Ary Syofian; Nurzi Sebrina (Universitas Negeri Padang, 2021)
The purpose of this research is to examine the effect of underwriter's reputation, auditor reputation, and firm size on underpricing. This research is classified as causative research with a quantitative approach. The population are IPO companies listed on the Indonesia Stock Exchange period of 2014 to 2018. By using the purposive sampling method, there were 83 companies as the research’s sample. The type of data used is secondary data obtained from the official site of the Indonesia Stock Exchange and the company's official website. The Hypothesis were tests using multiple linear regression analysis. The results indicate that the underwriter's reputation has a significant negative effect on underpricing level, and the auditor's reputation and firm size has not effect on underpricing.